KEMAMPUAN PROFITABILITAS DAN GROWTH OPPORTUNITY MEMODERASI PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Savitri, Ni Luh Asri; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to investigate the effect of corporate social responsibility disclosure on the company’s value, profitability and growth opportunity as the moderating variables. There were 53 companies engaged in agriculture and mining used as sample of this study. Those companies had been listed in stock exchange from 2009 to 2013. Furthermore, the multiple regression analysis is applied to test the hypothesis of this study. The result of the investigation shows that the CSR disclosure has positive effect towards the company’s value. Whereas, profitability and growth opportunity, that are used as moderation variables in relation to the CSR disclosure and company’s value, do not have significant effect.
Keywords: CSR Disclosure, Company’s Value, Profitability, Growth Opportunity